 ×     #### Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Click to Chat

1800-1023-196

+91-120-4616500

CART 0

• 0

MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping
```
F(x)=3x-1 and g(x)=x(x-1) then g(f^-1(x)) is ;??? a) (x/3)(x+1) b) (x/3)(x-1) c) 3x(3x-1) d) (x/3)(x/3 +1)
F(x)=3x-1 and g(x)=x(x-1) then g(f^-1(x)) is ;??? a) (x/3)(x+1) b) (x/3)(x-1) c) 3x(3x-1) d) (x/3)(x/3 +1)

```
2 years ago

```							f(x)=y=3x-1switching the variables to find the inverse function;x=3y-1y=(x+1)/3thus f-¹(x)=(x+1)/3g(f-¹(x))=f-¹(x)(f-¹(x)-1)=((x+1)/3)*((x+1)/3)-1)= ((x+1)/3)*((x+1–3)/3)= ((x+1)(x-2))/9= (x^2 - x - 2)/9
```
2 years ago
Think You Can Provide A Better Answer ?

## Other Related Questions on IIT JEE Entrance Exam

View all Questions »  ### Course Features

• 731 Video Lectures
• Revision Notes
• Previous Year Papers
• Mind Map
• Study Planner
• NCERT Solutions
• Discussion Forum
• Test paper with Video Solution  ### Course Features

• 731 Video Lectures
• Revision Notes
• Test paper with Video Solution
• Mind Map
• Study Planner
• NCERT Solutions
• Discussion Forum
• Previous Year Exam Questions